Identifikasi Senyawa Terpenoid dan Steroid pada Beberapa Tanaman Menggunakan Pelarut N-Heksan - Angel Novia Fransiska; Diba Masyrofah; Hermin Marlian; Irene Virda Sakina; Putri Setya Tyasna (Jurnal Health Sains, 2021)
Hexane is a hydrocarbon compound of alkanes with the chemical formula C6H14. The prefix hex refers to the six carbon atoms found in the hexane and the suffix ana is derived from the word alkane which refers to the single bond connecting the carbon atoms. Identification of terpenoid compounds and steroids has been identified in several plants, namely Red Shoots (Syzygium myrtifolium Walp.), Salam (Syzygium polyanthum), bilaran Tapah (Argyreia nervosa (Burm. F.), Blind (Excoecaria agallocha L.), as well as on the lotion preparations Citrus hystrix DC. This study was conducted to determine the content of terpenoid compounds and steroids found in some parts of plants using n-hexane solvents. Research used is qualitative research with Lieberman Burchard method. Review this article using a method of literature study by searching sources and literature with data form in the form of national journals to international journals about the last 10 years (2012-2021). Identification is carried out on extracts, fractions, isolates and lotion preparations using liquid vacuum chromatography, column chromatography, thin-layer chromatography, and Lieberman-Burchard reagents. The results showed that all of the samples were positive for terpenoid compounds and steroids using n-hexane solvents.